Students’ Translation Quality in Translating Local Animated Movie into English: A Case of Children Movie Translation - Nur Rosita; Anisa Nurjanah; Maulluddul Haq; Sayid Arshad Al Hindwan (English Department FBS UNP, 2025)
The rapid growth of film industry opens an opportunity for local film to be well-known abroad. Meanwhile, it is crucial to change the local identity in this case its language from the source language to target language in the movie in a proper way. This study is aimed to analyze the students’ translation quality in audiovisual translation such as film. The quantitative research model followed by qualitative description is applied in this study to assess students’ translation quality indicators which are accuracy, clarity, and readability in translating Indonesian children animated movie into English. “Candy Monster” movie is chosen as the source of the data because this movie is one of local movie which is well-know and internationally recognized in international movie industry. There are 35 sentences in the movie that has been translated by 23 students. The total data are 805 translation results. It is found that the students’ translation quality in the given task is the level of highly accurate, highly clear, and high readable. It can be concluded that the students have a good translation skill to translate this type of audiovisual media since it contains a simple and understandable sentences for the kids as the target audience of the movie.